ANALISIS KEPUASAN PASIEN BPJS TERHADAP PELAYANAN FARMASI DI FASILITAS KESEHATAN TINGKAT PERTAMA - Siti Rahmawati (Journal of Innovation Research and Knowledge, 2025)
Pharmaceutical Care at Primary Health Care Facilities play a crucial role in ensuring the success of Indonesia’s National Health Insurance (JKN) program. High-quality pharmacy services are essential to improve patient satisfaction, trust, and adherence to medication therapy. This study aimed to analyze the level of satisfaction among BPJS patients toward pharmaceutical care in Malang City using the SERVQUAL model, which includes five dimensions: reliability, responsiveness, assurance, empathy, and tangibles. A descriptive-analytic design with a cross-sectional approach was employed, involving 290 BPJS participants who received prescription services. Data were collected using a structured questionnaire and analyzed descriptively with SPSS version 25. The findings revealed that the overall patient satisfaction level was high, with the highest score found in the assurance dimension (93%), reflecting strong patient confidence in the pharmacists’ competence. Conversely, the reliability dimension had the lowest score (87%), particularly in aspects related to drug availability and clarity of medication instructions. This result indicates a service gap between professional competence and operational reliability. The study highlights the need for better integration between clinical and operational aspects of pharmaceutical care. Improving communication, stock management, and service efficiency is essential to enhance the overall quality of pharmacy services at PHCFs and to strengthen patient-centered care.